The Effectiveness Diabetic Foot Care by Modern Dressing in Sanglah Hospital and Dhalia Care Clinic. - Ni Made Shinta Tiara Dewi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Diabetes Mellitus (DM) is a chronic carbohydrate metabolism disturbance which has many long term complications, including diabetic foot that in latter stage can result amputation. Wound care is the one of nursing interventions intended to minimized the risk of getting amputation. One of the principles in wound care are giving a moist and warm environment in order to improve wound healing process. Beside that, wound care should be cost effective, meaning that is has not always cheap but it can benefit for patients. The value of chronic wound care can be estimated by evaluating the progress of the wound and total of cost that was spent.This research was a quasy eksperiment non equivalent control group desaign with a prospective approach. Samples randomly selected using a purposive sampling technique. The instruments used were Bates-Jansen wound assessment and the documentation of wound care material cost. The effectiveness of diabetic foot wound care using modern and conventional dressing was analyzed using One-Way Anova test with 95% confidence interval. The results showed that sig = 0,000 for score decrease in degree of wound and sig = 0,019 for total cost in wound care. Both of these variables that is benchmark effectiveness in wound care showed sig value < ? (0,05), so refuse H0 which means there is difference in effectiveness of diabetic foot care using modern dressing. Thereform it is recommended that health professionals should improve diabetic ulcer care methods using modern dressing as a choice in wound care.